Social Media Support and Funding Assistance for Psychological Injuries in Social Work - Hu, Xiaowu; Tang, Caiyi; Wang, Dongmei (Frontiers in Public Health, 2022)
There is an increasing number of psychological injuries in the process of urbanization and marketization in modern china. It is becoming a much serious social issue of this kind of mental health which influences millions of Chinese people and families. Reviewing and discussing the shorts of traditional therapies on the psychological injuries in social work practices of case work of clinic , group work and community work, and the media policy and social media appliance along with the function of the charity funds, This paper focuses on social media support and funding assistance that could play useful roles in helping to treat psychological injuries among social workers and their clients in the developed Internet society in China today. This paper sets up a new mechanism of social media marketing strategies and functional activities to the resolution for the psychological injuries out of the disease trap in China on the base of semi-structure interview with the expertise.